A Qualitative Investigation of Athletes' Views on Clean Sport - Beatričė Hoppen; Saulius Šukys (Lithuanian Sports University, 2023)
Background. Doping is a real problem in sport and continues to be one of the most controversial topics, despite significant advancements in doping prevention. Lack of knowledge of the anti-doping regulations is one of the risk factors for doping. Currently, anti-doping education is focused on clean sport promotion. Therefore, the aim of this study is to explore the views on clean sport and doping prevention among athletes from various sports. Methods. A qualitative approach was used to examine athletes' views on clean sport. Following a purposeful sampling technique, we interviewed eight men and one woman (Mage = 24.00, SD = 2.73 years) who were competing in various sports at the national level or above in Lithuania. Reflexive thematic analysis was used to analyse the data. Results. Analysis of interview data allowed to distinguish the following three broad themes related to athletes' views on doping education and recommendations for improving it. The research participants shared their thoughts about the concept of clean sport, possible reasons that may encourage athletes to compete in sport clean, and discussed clean sport education. Conclusion. Clean sport can be understood as cheating-free sport. Possible reasons to compete clean in sport are unwillingness to experience shame and fear of damaging health. Athletes believe that current doping prevention is ineffective. Our findings show the importance of clean sport education for young athletes, however, adult education about clean sport could be more difficult. Keywords: doping, clean sport, anti-doping education.